Basic anatomy for the manga artist : everything you need to start drawing authentic manga characters - Hart, Christopher, 1957- (Watson-Guptill Publications, 2011)
This book is loaded with clear step-by-step instructions and illustrations, anatomical charts and information, and before-and-after comparisons you won?t find anywhere else?all tailored to creating authentic Japanese-style manga.-From the Publisher.